2017
DOI: 10.1002/2016gc006782
|View full text |Cite
|
Sign up to set email alerts
|

The potential of sedimentary foraminiferal rare earth element patterns to trace water masses in the past

Abstract: Dissolved rare earth element (REE) concentration data from intermediate and deep seawater form an array characterized by higher middle‐REE enrichments (MREE/MREE*) in the North Atlantic and a progressive increase in heavy‐to‐light REE ratios (HREE/LREE) as water masses age. The REEs in foraminifera are fractionated toward higher MREE/MREE* and lower HREE/LREE relative to seawater. Calculations based on a scavenging model show that the REE patterns in uncleaned core‐top foraminifera resemble those adsorbed onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 72 publications
4
55
0
4
Order By: Relevance
“…Station 21-1 (this study) is also shown in order to evaluate differences with respect to SEqPIW, which dominates the intermediate water at this location. In general, all samples have lower LREE concentrations compared with original AAIW, which is expected as the more readily scavenged LREEs are preferentially removed from the water column as the water masses age (e.g., Osborne et al, 2017). The fact that the source AAIW normalized REEs are <1, especially for the LREEs, clearly indicates the importance of removal by particles during transit through the gyre, despite relatively low productivity.…”
Section: Mixing Of Southern Ocean Derived Water Masses Along the Soutmentioning
confidence: 88%
See 1 more Smart Citation
“…Station 21-1 (this study) is also shown in order to evaluate differences with respect to SEqPIW, which dominates the intermediate water at this location. In general, all samples have lower LREE concentrations compared with original AAIW, which is expected as the more readily scavenged LREEs are preferentially removed from the water column as the water masses age (e.g., Osborne et al, 2017). The fact that the source AAIW normalized REEs are <1, especially for the LREEs, clearly indicates the importance of removal by particles during transit through the gyre, despite relatively low productivity.…”
Section: Mixing Of Southern Ocean Derived Water Masses Along the Soutmentioning
confidence: 88%
“…All samples were filtered directly from the Niskin bottles using AcroPak500 filter cartridges with 0.8/0.2 µm pore size into acid-cleaned PE bottles and cubitainers, 125 ml for REE analysis and 10 L for Nd isotope compositions, respectively. All samples were acidified to pH 2 onboard using distilled 6 N HCl and were stored at 4 • C. REE concentrations for profile 21-1 (except for 5,172 m) and sample 53-4-3088 m were previously published in Osborne et al (2017).…”
Section: Sampling At Tahiti and Above The Manihiki Plateaumentioning
confidence: 99%
“…The PAAS‐normalized distribution of rare earth elements at 2.37 km (TR163‐14) and 3.2 km (TR163‐20B) compared to published eastern equatorial Pacific core top data from cores TR163‐11, TR163‐14, and VM28‐139 (Osborne et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, riverine input and alteration of basalts are also important sources and sinks of Li to sediments (Elderfield & Schultz, 1996) and high Figure 6. The PAAS-normalized distribution of rare earth elements at 2.37 km (TR163-14) and 3.2 km (TR163-20B) compared to published eastern equatorial Pacific core top data from cores TR163-11, TR163-14, and VM28-139 (Osborne et al, 2017).…”
Section: The Influence Of the Panama Basin Geochemical Environment Onmentioning
confidence: 99%
“…Several reasons for these interspecific differences can be advanced. It is known that oysters can be selective in their diet, composed mainly of diatoms (Yonge, 1928;Paulmier, 1971) of a specific size range, and preferentially digest specific species of diatoms over others (Shumway et al, 1985;Cognie et al, 2001). If food is a source of REEs, it may be possible that each oyster species does not feed on the same prey, which can present different abundances of these elements.…”
Section: Discussionmentioning
confidence: 99%